2019
DOI: 10.25186/cs.v14i1.1522
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Variables and Sensorial Quality of Coffee in the Mantiqueira Region of Minas Gerais

Abstract: <p>The objective of this study was to identify meteorological variables related to the sensorial quality of the coffees from Mantiqueira region in Minas Gerais.  Meteorological conditions are strongly related to the coffee’s sensorial characteristics, however, there aren’t many studies quantifying this relation. Air temperature and rainfall data were collected and spatialized for regional analysis. These were associated to the 2007 through 2011 coffees’ beverage scores. The region is stratified according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…These results indicate that both the effects of genotypes (clones) and the effect of the GxE interaction are important for the expression of the beverage quality. Significant effects of the genotype × environment interaction in coffee growing were also reported in other studies (Barbosa et al, 2012;Borém et al, 2019;Laviola et al, 2007;Fonseca et al, 2019;Moura et al, 2017).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These results indicate that both the effects of genotypes (clones) and the effect of the GxE interaction are important for the expression of the beverage quality. Significant effects of the genotype × environment interaction in coffee growing were also reported in other studies (Barbosa et al, 2012;Borém et al, 2019;Laviola et al, 2007;Fonseca et al, 2019;Moura et al, 2017).…”
Section: Resultssupporting
confidence: 83%
“…Similar results were found by Cabrera, Acevedo and Lacerra (1991) in their studies conducted in the mountainous area of Cuba and by Buenaventura and Casteño (2002) in Colombia in crops planted at three different altitudes. Others studies also observed that the higher the altitude, the higher the scores for beverage quality in arabica coffee (Barbosa et al, 2012, Borém et al, 2019Rodrigues et al, 2016).…”
Section: Statistical Analysesmentioning
confidence: 89%
“…A mesorregião sul de Minas Gerais apresenta atributos geográficos e condições climáticas desejáveis para o desenvolvimento da cultura do café (BORÉM, et al 2019). As classes climáticas para a mesorregião são Cwb (56%), classificado como clima temperado úmido e inverno seco, precipitação média anual de 1500 mm, de maior concentração entre os meses de novembro a fevereiro e temperatura média no verão inferior a 22ºC e superior a 10ºC durante o inverno; Cwa (44%), classificado como clima temperado úmido e inverno seco.…”
Section: Methodsunclassified
“…As condições de produção na região permitem níveis de produtividade relativamente estáveis, além da melhor qualidade sensorial. Borém et al (2019) identificaram que na região da Mantiqueira de Minas, acima de 1000 m ocorre menor amplitude térmica do ar, o que proporciona cafés com qualidade superior.…”
Section: Colheitaunclassified
“…Climate, soil, topography, altitude range, latitude (Bertrand et al, ; Figueiredo et al, ), hydrography, as well as conservation status or degradation level are some of the environmental aspects affecting coffee quality (Alpizar & Bertrand, ; Tolessa, D'heer, Duchateau, & Boeckx, ). The effects of altitude in association with temperature have been described in several studies around the world as the main factors affecting coffee quality (Borém et al, ; Buenaventura‐Serrano & Castaño‐Castrillón, ; Decazy et al, ; Joët et al, ; Scholz et al, ; Silveira et al, ).…”
Section: Introductionmentioning
confidence: 99%